Observation of frequency division and chaos behavior in a laser diode driven by a resonant tunneling diode - Romeira, B.; Figueiredo, J.; Slight, T.; Wang, L.; Wasige, E.; Ironside, Charlie; Quintana, J.; Avedillo, M. (2008)
We report optical experimental frequency division and chaos results in a resonant tunneling diode laser diode driver configuration that forms a self-oscillating circuit. Circuit behavior and laser output results are well predicted using Liénad's equation. © 2008 Optical Society of America.